Pola Investasi Tenaga Kerja Indonesia (TKI) Di Kecamatan Lembeyan Kabupaten Magetan - Danang Hadi Saputro; Ninik Srijani; Novita Erliana Sari (Universitas PGRI Madiun, 2021)
This study aims to determine the investment pattern of TKI in Lembeyan District, Magetan Regency. There are 15 informants who have worked abroad with 1 departure. This type of research is qualitative with data collection techniques, observation, interviews, documentation, and triangulation. Data analysis in this study used data reduction, data presentation and data verification. The results of this study indicate: (1) The people of Lembeyan District, Magetan Regency, decided to become migrant workers because they wanted to improve their economic conditions and seek investment capital. (2) The attractiveness of becoming a TKI is due to the high salary and environmental influences. (3) The TKI's income is sufficient to make investments. (4) TKI divides their income to send it to their families and save it. (5) TKI can arrange expenses as needed. (6) their finances after working abroad are sufficient for their needs. (7) TKI understands investment. (8) TKIs have financial plans before retiring from work abroad. (9) Almost all TKI from Lembeyan have no investment barriers. (10) Property investment is the most preferred choice for TKI Lembeyan